Yellow pea flour and protein isolate as sources of antioxidant peptides after simulated gastrointestinal digestion - Cipollone, María Agustina (2020)
Although peas are widely consumed legumes throughout the world, the bioactivity of the peptides released by the gastrointestinal digestion has not been sufficiently studied so far. The objective of the present work was to evaluate the potential of flours and protein isolates obtained from two varieties of yellow peas as sources of antioxidant peptides. Flours and protein isolates were prepared and submitted to a simulated gastrointestinal digestion. Protein hydrolysis degree (TNBS method) and protein solubility (in phosphate buffer saline, pH = 7.4) values were independent on the starting material. Antioxidant activity measured by oxygen radical absorbance capacity (ORAC) and hydroxyl radical averting capacity (HORAC) showed no differences between varieties. A lower activity was registered for protein isolates with respect to flours in the case of HORAC, which could be associated with a loss of molecules with molecular masses lower than 43 kDa in the protein isolates. A significant increase in activities was evidenced by both methods after gastrointestinal digestion, except in the case of HORAC activity of flours. Digested from protein isolates presented a greater ratio of molecules smaller than 1.4 kDa and a lower ratio of those larger than 6.5 kDa with respect to digested flours, according to electrophoresis and gel filtration chromatography studies. Results suggested that the presence of other components or/and the initial state of proteins would affect proteolytic attack of digestive enzymes. Both, pea flours and protein isolates, present interesting potential as antioxidants food ingredients.